Effects of Big-Amplitude Calisthenic Group Exercises With Music on Balance, Cognition, Physical Activity, and Dual-Task Performance in Ambulatory Older Adults: A Randomized Clinical Study. - Fıçıcı, Zeynep; Aytutuldu, Güzin K. (Journal of Aging & Physical Activity, 2026)
Background/Objectives: Aging physical capacity and the ability to perform daily activities. This study aims to investigate the effects of music added to big-amplitude calisthenic group exercises on dual-task performance and balance in older adults. Methods: Fifty participants aged 65–80 years were randomly assigned to two groups (Group 1: M = 69.44 ± 3.88 years, Group 2: M = 68.76 ± 2.78 years). Group 1 performed a big-amplitude calisthenic exercise program accompanied by classical music, while Group 2 performed the same program without music. The intervention lasted 8 weeks with two 60-min sessions per week. Outcomes were assessed pre- and postintervention using the Mini-Mental State Examination, Mini-Balance Evaluation Systems Test, Dual-Task Questionnaire, Timed Up and Go (TUG) test, and the Physical Activity Scale for the Elderly. Results: Both groups improved significantly from baseline in Mini-Mental State Examination, Mini-Balance Evaluation Systems Test, Dual-Task Questionnaire, Physical Activity Scale for the Elderly, TUG, and TUG dual task (all p <.001). Group 1 demonstrated larger improvements across these outcomes compared with Group 2, with higher within-group effect sizes in the Mini-Mental State Examination (d = 0.98 vs. 0.29), Mini-Balance Evaluation Systems Test (d = 0.49 vs. 0.16), Dual-Task Questionnaire (d = 1.07 vs. 0.76), Physical Activity Scale for the Elderly (d = 0.82 vs. 0.15), TUG (d = 0.47 vs. 0.36), and TUG dual task (d = 0.56 vs. 0.48). Conclusion: Big-amplitude calisthenic group exercises appear to have beneficial effects on balance and dual-task performance in older adults, with music potentially enhancing these outcomes. Significance/Implications: Music-supported calisthenic exercises may promote cognitive–motor benefits in older adults, though the lack of a nonexercise control group and short follow-up limit the strength of conclusions.